FRI0387 ANTI-RNA polymerase III subset of scleroderma patients: a monocentric study. (15th June 2017) - Pigatto, E; Ferranti, M; Favaro, M; Polito, P; Zanatta, E; Galozzi, P; Tonello, M; Punzi, L; Cozzi, F
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by heterogeneous clinical features and variable disease course. Specific antinuclear antibodies (ANA) identify different clinical subsets and are very useful in defining the prognosis of the patients. Recently, the anti-RNA polymerase III antibodies (anti-RNAP) were defined as the third specific ANA of SSc, together with anti-centromere (ACA) and anti-topoisomerase I (anti-Scl70). Objectives: The aim of this study was to analyze the clinical picture of a group of SSc patients with anti-RNAP in a monocentric cohort of patients and to compare it with other subsets of patients with different specific ANA. In particular, the visceral involvement and the concomitant malignancies were investigated. Methods: Among the SSc patients referring to the Rheumatology Unit of Padova University, 49 cases with anti-RNAP specific ANA were considered. Patient's demographics data and major clinical manifestations were compared with those of 50 ACA-positive and 52 anti-Scl70-positive patients. The skin score and the presence of digital ulcers, arthritis, interstitial lung disease (ILD), cardiac involvement including pulmonary hypertension, gastrointestinal disease (GI) and scleroderma renal crisis (SRC) were assessed. The presence and type of concomitant malignancies were also evaluated. Results: 53% of anti-RNAP-positive patients had a diffuse cutaneous form of SSc. The skin score was significantly higher than in ACA-positive patients (p<0.001). Digital ulcers were active in 73.5% of cases, without significant difference with the other two subsets. Arthritis was found in 20.4% of cases in comparison to 4% in ACA-positive patients (p<0.02). Regarding visceral involvements, GI disease was the most common manifestation in all subsets; SRC was observed in 24.4% of anti-RNAP-positive patients and was significantly more frequent in comparison to ACA-positive (p<0.005); ILD showed a prevalence of 42.8% in anti-RNAP subset, lower than in anti-Scl70-positive (p<0.05) and higher than in ACA-positive patients (p<0.01); cardiac involvement was observed in 32.6% of anti-RNAP-positive patients, without significant difference with the other subsets. Malignancies were found in 33 (67.3%) anti-RNAP-, 18 (36%) anti-Scl70- and 7 (14%) ACA- positive patients. The most common cancer-sites were breast (36%), lung (14%) and colon (10%). The risk of developing cancer was higher in anti-RNAP-positive patients than in other subsets ( OR: 6.35). Conclusions: Our data demonstrated that anti-RNAP specific antibodies can identify a subset of SSc patients characterized by a severe clinical picture, with a high prevalence of diffuse cutaneous form, SRC, cardiac involvement and ILD. These patients showed also an elevated risk of developing cancer. Our results were consistent with recent published papers on this topic (1, 2). References: Terras S et al. RNA polymerase III autoantibodies may indicate renal and more severe skin involvement in systemic sclerosis. Int J Dermatol 2016; 55:882–5. Lazzaroni MG et al. Malignancies in patients with anti-RNA Polymerase III antibodies and Systemic Sclerosis: analysis of the EULAR Scleroderma Trials and Research Cohort and possible recommendations for screening. J Rheumatol 2017; pii: jrheum.160817. Disclosure of Interest: None declared